A Study of the Effects of Virtual Reality-Based Sports Games on Improving Executive and Cognitive Functions in Minors with ADHD—A Meta-Analysis of Randomized Controlled Trials - Weixiao Zhang; Haojie Li; Yi Sheng (Behavioral Sciences)
(1) Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common mental health condition in children that can significantly impact their quality of life. In this study, we compared the effectiveness of virtual reality (VR) technology with traditional rehabilitation training through meta-analysis, aiming to provide a basis for the clinical optimization of rehabilitation strategies. (2) Methods: The study was registered in PROSPERO, and a search was conducted using the subject terms “virtual reality” and “attention deficit hyperactivity disorder” across six databases. The search yielded 10 randomized controlled trials (RCTs) that met the inclusion criteria. The data were analyzed using a random-effects model in statistical software. (3) Results: The study found that VR exercise game technology significantly outperformed the control group in terms of both the primary outcome (executive function and cognitive function) and secondary outcomes (attention, memory, and task switching) in children under the age of 18 with ADHD (children under 18 years of age are defined as adolescents and children). Sensitivity analyses confirmed the robustness of the five outcome measures. Bias tests revealed no publication bias for the primary outcome, but some bias for the secondary outcomes, which did not affect the overall results. (4) Conclusion: VR motor games significantly improved the executive and cognitive functions of children with ADHD.